Abelacimab versus Rivaroxaban in Patients with Atrial Fibrillation - Ruff, Christian T; Patel, Siddharth M; Giugliano, Robert P; Morrow, David A; Hug, Bruce; Kuder, Julia F; Goodrich, Erica L; Chen, Shih-Ann; Goodman, Shaun G; Joung, Boyoung; Kiss, Robert G; Spinar, Jindrich; et al. (The New England journal of medicine, 2025)
BACKGROUND: Abelacimab is a fully human monoclonal antibody that binds to the inactive form of factor XI and blocks its activation. The safety of abelacimab as compared with a direct oral anticoagulant in patients with atrial fibrillation is unknown. METHODS: Patients with atrial fibrillation and a moderate-to-high risk of stroke were randomly assigned, in a 1:1:1 ratio, to receive subcutaneous injection of abelacimab (150 mg or 90 mg once monthly) administered in a blinded fashion or oral rivaroxaban (20 mg once daily) administered in an open-label fashion. The primary end point was major or clinically relevant nonmajor bleeding. RESULTS: A total of 1287 patients underwent randomization; the median age was 74 years, and 44% were women. At 3 months, the median reduction in free factor XI levels with abelacimab at a dose of 150 mg was 99% (interquartile range, 98 to 99) and with abelacimab at a dose of 90 mg was 97% (interquartile range, 51 to 99). The trial was stopped early on the recommendation of the independent data monitoring committee because of a greater-than-anticipated reduction in bleeding events with abelacimab. The incidence rate of major or clinically relevant nonmajor bleeding was 3.2 events per 100 person-years with 150-mg abelacimab and 2.6 events per 100 person-years with 90-mg abelacimab, as compared with 8.4 events per 100 person-years with rivaroxaban (hazard ratio for 150-mg abelacimab vs. rivaroxaban, 0.38 [95% confidence interval CI, 0.24 to 0.60]; hazard ratio for 90-mg abelacimab vs. rivaroxaban, 0.31 [95% CI, 0.19 to 0.51]; P<0.001 for both comparisons). The incidence and severity of adverse events appeared to be similar in the three groups. CONCLUSIONS: Among patients with atrial fibrillation who were at moderate-to-high risk for stroke, treatment with abelacimab resulted in markedly lower levels of free factor XI and fewer bleeding events than treatment with rivaroxaban. (Funded by Anthos Therapeutics; AZALEA-TIMI 71 ClinicalTrials.gov number, NCT04755283.).
Keywords: antikoagulancia; Female; faktor XI; Rivaroxaban; Atrial Fibrillation; ženské pohlaví; Anticoagulants; cévní mozková příhoda; krvácení; lidé; dvojitá slepá metoda; injekce subkutánní; Stroke; rivaroxaban; Factor XI; Aged, 80 and over; Double-Blind Method; Male; Factor Xa Inhibitors; Aged; aplikace orální; inhibitory faktoru Xa; Injections, Subcutaneous; Hemorrhage; fibrilace síní; humanizované monoklonální protilátky; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Antibodies, Monoclonal, Humanized; Administration, Oral; Middle Aged; Humans